Training of Trainers (TOT) Data Science for Teaching Doctors - Rinabi Tanamal; Felicia Graciella; Michelle Chandra; Trianggoro Wiradinata; Yosua Soekamto; Theresia Ratih Dewi Saputri (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Due to the rapid development of technology, technology has become very attached to various fields in Indonesia. The health sector is no exception. If more and more data in the health sector is used properly, it will provide good benefits for the world of health and patients. Therefore, a Data Science Training of Trainers Activity was held for Doctors by the Profession of Doctors at Universitas Ciputra Surabaya. Activities are carried out by providing materials and working on questions by the doctors involved. Thus, it is hoped that the doctors participating in this activity can provide medical literacy knowledge to prospective doctor students at Universitas Ciputra. From the results of this TOT evaluation, it has a positive impact on doctors regarding alternative ways to process the data needed for medical research.